Kewenangan Polisi Perairan Dan Udara Di Wilayah Perairan Kabupaten Kepulauan Aru - Soenarjo, Raimondo Delly Jones; Pietersz, Jemmy Jefry; Mustamu, Julista (Bacarita Law Journal, 2024)
It is necessary to carry out the authority of law enforcement in the seas and waters of Indonesia, especially in the Aru Islands Regency. This is considered important because the territorial waters of the Aru Archipelago Regency are cross-shipping and various crimes often occur, namely illegal fishing and illegal logging. This is a challenge for the regional government and even law enforcement for the Air and Water Police Unit. The purpose of this paper is to know and analyze the regulations regarding law enforcement in the territorial waters of the Aru Islands Regency and the authority of the Water Police in law enforcement in the Aru Islands Regency Territorial Waters. This research method uses a normative type of research using a statutory approach and a conceptual approach. The legal materials used are primary and secondary legal materials. The results showed that in law enforcement arrangements in the waters there is often overlap in the main tasks and functions of each law enforcement apparatus at sea. However, regulation of law enforcement in the territorial waters of the Aru Islands Regency is a must in maintaining the integrity of the national defense and especially for the welfare of the community in a sustainable manner, considering that the marine and fishery resources in the marine area of ​​the Aru Islands Regency have high economic value. so that the authority of the Satpolair as the executor of the preventive and repressive functions of the police in law enforcement in the territorial waters carries out water patrols and takes action against violations that occur in the territorial waters. However, there are still several law enforcement mechanisms that need coordination between related agencies so that law enforcement can be carried out in accordance with the applicable mechanism.